PENGEMBANGAN MULTIPLE INTELLIGENCES MELALUI KEGIATAN EKSTRAKULIKULER DI MI KHADIJAH MALANG - Irsyadila Khuzludani; Mohammad Afifulloh; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
The research that conducted is about the development of multiple intelligences through extracurricular activities in Madrasah Ibtidaiyah Khadijah Malang. The research method used is qualitative research. The data collection techniques used are observations, interviews and documentation. The implementation of extracurricular activities is carried out according to extracurricular type characteristics. The implementation of extracurricular activities is the development of compound intelligence (multiple intelligences) of MI Khadijah. Multiple intelligences are theories triggered by Howard Gardner. Gardner's intelligence is divided into 9 types, namely visual-spatial intelligence, language intelligence, interpersonal intelligence, intrapersonal intelligence, Music intelligence, bodily-kinesthetic intelligence, mathematical logical intelligence, naturalist intelligence and existential intelligence. Extracurricular activities in MI Khadijah there are 12 extracurricular. Extracurricular activities also become a container in developing students' talents and interests. Students who have potential in multiple intelligences will be able to solve a problem and can produce a masterpiece. The constraints of the implementation of extracurricular activities in MI Khadijah that related to compound intelligence are the weakness of students in interpersonal intelligence, intrapersonal Intelligence, language intelligence, naturalist intelligence, and logical-mathematical intelligence.